Psychometric properties of the Persian version of delivery fear scale (DFS) in Iran - Aazam Shakarami; Mina Iravani; Mojgan Mirghafourvand; Mohammad Asghari Jafarabadi (BMC, 2021)
Abstract Background The aim of the present study was to evaluate the psychometric properties of the Persian version of delivery fear scale (DFS) among Iranian women population. Methods This is a methodological study that was conducted to evaluate the psychometric properties of DFS. Convenience sampling was used to select 200 pregnant women from the maternity ward of Razi Hospital in Ahvaz, Iran. In the first step, the scale was translated into Persian using backward-forward translation method. Afterwards, the following types of validity were examined: face validity based on impact score, construct validity based on confirmatory factor analysis (CFA), and concurrent validity. The Pearson correlation test was used to determine the correlation of DFS with pregnancy-related anxiety questionnaire (PRAQ), Childbirth Attitude Questionnaire (CAQ), Spielberger's state-trait anxiety inventory (STAI), and the short form of Lowe's childbirth self-efficacy inventory. Reliability of DFS was assessed by determining internal consistency (Cronbach's alpha) and split-half method. Results CFA had satisfactory validity considering x2⁄df < 5 and the RMSEA < 0.08. /the obtained Cronbach's alpha coefficient was 0.77. The split-half coefficient of the questionnaire was 0.83, indicating an acceptable reliability for the questionnaire. The results showed that DFS had a direct significant correlation with the CAQ (r = 0.72), PRAQ (r = 0.74), STAI-Y1 (r = 0.71) and STAI-Y1 (r = 0.63) and a reverse significant correlation with subscales of the short form of Lowe's childbirth self-efficacy inventory including outcome expectancy (r= -0.75) and self-efficacy expectancy (r= -0.76). Conclusions The findings of the present study confirm the validity and reliability of the Persian version of DFS as an instrument for measuring fear of childbirth (FOC) in Iranian women population.